Emergence of vanA vancomycin-resistant Enterococcus faecium in a hospital in Porto Alegre, South Brazil - Mariah Resende; Juliana Caierão; Juliana Gil Prates; Gabriel Azambuja Narvaez; Cícero Armídio Gomes Dias; Pedro Alves d'Azevedo (Journal of Infection in Developing Countries)
Introduction: In Porto Alegre (South Brazil), since the first VRE isolation in 2000 until the middle of the last decade, the epidemiology of enterococcal infections presented the peculiarity that, as opposed to other regions of the country, almost all VRE were E. faecalis. The aim of this study was to investigate the microbiological and epidemiological characteristics of a VRE outbreak that occurred between August 2010 and September 2011 in Porto Alegre, South Brazil. Methodology: Twenty-nine isolates from inpatients of Mãe de Deus Hospital that were identified and characterized for their susceptibility profile, vancomycin genotype, presence of esp gene, biofilm production, and clonal relationship were collected.  Patients’ records were reviewed for clinical information. Results: All isolates were identified as vancomycin/ampicillin resistant E. faecium carrying the vanA gene. Almost all were susceptible to gentamicin and streptomycin. Most patients died and were associated with a hemodialysis unit stay. All but the first isolate were clustered in a main clone. Conclusions: An important change in vancomycin-resistant enterococci was observed. Studies like this are necessary to monitor the dissemination of VRE, especially of some individual clones.